Adhesion of Porphyromonas gingivalis and Biofilm Formation on Different Types of Orthodontic Brackets - William Papaioannou; Athanasios Panagopoulos; Haroula Koletsi-Kounari; Efterpi Kontou; Margarita Makou (Hindawi Limited, 2012)
Objectives. To examine the interaction between Porphyromonas gingivalis and 3 different orthodontic brackets in vitro, focusing on the effect of an early salivary pellicle and other bacteria on the formation of biofilms. Material and Methods. Mono- and multi-species P. gingivalis biofilms were allowed to form in vitro, on 3 different bracket types (stainless steel, ceramic and plastic) with and without an early salivary pellicle. The brackets were anaerobically incubated for 3 days in Brain Heart Infusion Broth to form biofilms. Bacteria were quantified by trypsin treatment and enumeration of the total viable counts of bacteria recovered. Results. Saliva was found to significantly affect (𝑃<0.001) adhesion and biofilm formation of P. gingivalis, with higher numbers for the coated brackets. No significant effect was detected for the impact of the type of biofilm, although on stainless steel and plastic brackets there was a tendency for higher numbers of the pathogen in multi-species biofilms. Bracket material alone was not found to affect the number of bacteria. Conclusions. The salivary pellicle seems to facilitate the adhesion of P. gingivalis and biofilm formation on orthodontic brackets, while the material comprising the brackets does not significantly impact on the number of bacteria.